Enhancement of dielectric properties of PMMA:TiO2 nanocomposite for organic field effect transistors / Lyly Nyl Ismail - Ismail, Lyly Nyl (2015)
In this thesis, a composite between poly (methyl methacrylate) (PMMA) with titanium dioxide (Ti02) films were synthesized, fabricated and characterized using sol-gel spin coating technique. The dielectric, electrical and physical properties of PMMA:Ti02 nanocomposite films was were investigated, to be used as the dielectric layer in the metal-insulator-semiconductor (MIS) device and organic field effect transistors (OFET) application. The goal of this study is to enhance the dielectric properties of PMMA with the influence of TiC^nanopowder (high-A;) material in the PMMA. Another goal is to overcome the leakage current (tunnelling current) and high operating voltage in MIS and OFET devices. PMMA:TiC>2 nanocomposite dielectric films deposition parameter were optimized resulting in good dielectric, electrical and physical properties. Results from the parameter optimization showed that the dielectric properties of PMMA:Ti02 nanocomposite film, which is focusing on the real permittivity, e\ imaginary permittivity, 6" and capacitance were improved. The real permittivity, e' of PMMA:Ti02 nanocomposite film was 12 and 10 measured at 1 kHz and 1MHz, respectively. These values are higher than pure PMMA film which was 4.6 and 2.9, respectively measured at the same frequency. The capacitance value for PMMA:Ti02 nanocomposite film increased drastically from 296 pF/cm2 (for pure PMMA) to 457 9 o nF/cm . The leakage current density for PMMA:Ti02 nanocomposite film was ~ 10" A/cm2 under small electric field of 0.25 MV/cm is due to the addition of Ti02 nanoparticles. Metal-insulator-semiconductor (MIS) structure was used to investigate the compatibility of PMMA:TiC>2 nanocomposite film to be used as dielectric layer with ZnO and P3HT semiconductor layers. The capacitance-voltage (C-V) characteristics indicated that density of interface of trapped charge was found to be 9 x 109 eV_1cm'2. In addition, the MIS exhibited leakage current of 10"6 A/cm2 at IV and relatively high breakdown voltage (2.05MV/cm). Small hysteresis was observed in C-V and I-V characteristics which were associated with ion drift and polarisation of the PMMA:Ti02 nanocomposite dielectric film. Finally, OFET devices with PMMA:TiC>2 nanocomposite as gate dielectric were demonstrated. The OFET performance proved that PMMA:Ti02 nanocomposite dielectric films were compatible with organic and inorganic semiconductors. Low threshold voltage, VTH was obtained for n-type and p-type OFET was around 2 V and -3 V respectively, due to the increment in the e' and capacitance value of the PMMA:Ti02 nanocomposite dielectric film. The fabricated OFET using PMMA:Ti02 as dielectric layer showed almost comparable characteristics reported by other researcher.